2017
DOI: 10.1111/jan.13501
|View full text |Cite
|
Sign up to set email alerts
|

Mediating role of psychological well‐being in the relationship between organizational support and nurses’ outcomes: A cross‐sectional study

Abstract: The findings suggest that organizational support for nursing practice and psychological well-being are two factors that contribute to caring behaviour of nurses and their job satisfaction. Also, positively perceived organizational support generates favourable psychological well-being which in turn enhances nurses' quality of care and job satisfaction. The findings highlight the importance of establishing a supportive nurse practice environment and paying attention to the nurses' psychological well-being in hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
80
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(88 citation statements)
references
References 54 publications
8
80
0
Order By: Relevance
“…It has been confirmed that a low level of justice contributes to impairments in the health outcomes and emotional states of employees (Elovainio, Heponiemi, Sinervo, & Magnavita, ). Nurses who have a good psychological and physiological state will be more active in their work and adopt good work behaviours that promote nursing care quality (Pahlevan Sharif, Ahadzadeh, & Sharif Nia, ). Organizations have to improve organizational justice, which enhances the psychological resources, and thereby, improve the efficiency of nursing care.…”
Section: Discussionmentioning
confidence: 99%
“…It has been confirmed that a low level of justice contributes to impairments in the health outcomes and emotional states of employees (Elovainio, Heponiemi, Sinervo, & Magnavita, ). Nurses who have a good psychological and physiological state will be more active in their work and adopt good work behaviours that promote nursing care quality (Pahlevan Sharif, Ahadzadeh, & Sharif Nia, ). Organizations have to improve organizational justice, which enhances the psychological resources, and thereby, improve the efficiency of nursing care.…”
Section: Discussionmentioning
confidence: 99%
“…Job satisfaction is affected by many factors and organizational support and job control have a predictive effect on job satisfaction. Many studies have suggested that perceived organizational support can promote nurses' satisfaction (Chevalier et al, 2017;Shao, Zhang, & Chen, 2016;Sharif, Ahadzadeh, & Nia, 2018). A good sense of organizational support enables nurses to perceive the organization's respect, concern and attention, generating a strong sense of security and belonging (Eisenberger, Armeli, Rexwinkel, Lynch, & Rhoades, 2001).…”
Section: Itsmentioning
confidence: 99%
“…Although the association of work environment with work attitude has been widely investigated in hospital nurses, the underlying mechanism of this relationship has been less explored. A few researchers have examined the mediating role of psychological characteristics, such as resilience, work engagement and psychological well‐being, on the associations between work environment and work attitudes (Liu & Aungsuroch, ; Pahlevan Sharif, Ahadzadeh, & Sharif Nia, ). Additional mediators should be explored to explain how work environment influences work attitudes.…”
Section: Introductionmentioning
confidence: 99%